Evaluating the accuracy and reliability of fonseca anamnestic index (FAI) in screening temporomandibular disorders - Nguyen, Minh Quan; Nguyen, Cong Sinh; Nguyen, Gia Kieu Ngan (Tạp chí Y Dược Huế, 2024)
Background: Temporomandibular disorders (TMD) are a common medical condition in Vietnam and around the world. Fonseca Anamnestic Index (FAI) is a quick and simple questionnaire to diagnose TMD. Objectives: (1) To evaluate the accuracy and reliability of FAI in the diagnosis of TMD and (2) to suggest adjustments to enhance the clinical value of FAI. Material and method: This study included 198 students (69 males, 129 females) from the Faculty of Odonto-Stomatology, Hue University of Medicine and Pharmacy. This study is conducted from 06/2022 to 12/2022. Participants initially filled out FAI questionnaire, then followed by questionnaire and clinical examination using Diagnostic Criteria for Temporomandibular Disorder (DC/TMD) as a gold standard. Results: According to DC/TMD, the prevalence of TMD among students was 34.8%. FAI had high sensitivity (97.1%) but low specificity (40.46%) (cutoff point = 17.5), Cronbach Alpha value was 0.684. The suggested cutoff point was calculated at 22.5. Only Question 8 from FAI questionnaire showed insignificant difference between TMD and non-TMD group. By extracting the 8th question with the cutoff point at 22.5, the sensitivity and specificity of the modified questionnaire was 82.1% and 64.9% respectively and the Cronbach Alpha value mildly increased to 0.692. Conclusion: The FAI is suited for screening patients with TMD because of its high sensitivity. However, FAI low specificity makes it not optimal for efficiently diagnosing TMD. It is suggested to modify the FAI by eliminating the 8th question in the questionnaire and have a higher cutoff point (23).